Toxicity profile characteristics of novel androgen-deprivation therapy agents in patients with prostate cancer: a meta-analysis. Issue 2 (1st February 2018) - Zhu, Jianhong; Liao, Rifang; Su, Chen; Liang, Dan; Wu, Junyan; Qiu, Kaifeng; Li, Jianfang
ABSTRACT: Background : To investigate the toxicity profile characteristics of abiraterone acetate and enzalutamide to see if they are of critical clinical value. Methods : Prospective studies were identified by searching the PubMed, EMBASE, Cochrane Library, and American Society of Clinical Oncology Meeting abstracts. Randomized clinical trials that evaluate abiraterone acetate or enzalutamide in patients with prostate cancer were included. The risk ratio (RR) of adverse events (AEs) was calculated for each trial along with appropriate 95% CI using fixed- or random-effects methods. Results : Ten studies (5 abiraterone acetate, and 5 enzalutamide studies) were included in the meta-analysis. Use of abiraterone acetate was associated with an increased risk of all-grade adverse effects (RR = 1.01, 95% CI: 1.01–1.02) and high-grade adverse effects (RR = 1.29, 95% CI: 1.15–1.45). Also, there was a significantly higher incidence of some individual adverse effects (e.g. liver-function test abnormalities, arthralgia, cardiac adverse effects, diarrhea, oedema, hypertension and hypokalemia). Treatment with enzalutamide did not increase the risk of all-grade adverse effects and high-grade adverse effects, but there was a significantly higher incidence of some individual adverse effects (e.g. back pain, fatigue, hot flush and hypertension). Conclusions : Both abiraterone acetate and enzalutamide have toxicity profile characteristics that need to be recognized. Understanding the toxicity profile characteristics of both drugs could promote decision making in clinical use.